Strengthening public health contracting: findings of a follow-up nationwide survey from Aotearoa - Came H; Baker M; McKenna B; McCreanor T (Informa UK Limited, trading as Taylor & Francis Group, 2022)
In 2010 and 2015 nationwide surveys monitored government management of public health providers. These surveys found evidence of inconsistent management which disadvantaged Māori providers, consistent with institutional racism. In Dec 2019 to March 2020 a follow-up nationwide telephone survey was completed. Public health units, primary health organisations, Māori health providers and non-governmental organisations with public health contracts responded (72%). This paper focuses on the findings about (i) contracts, and (ii) relationships. Descriptive statistical analysis was applied to quantitative responses and explanatory and combinatory analyses informed by thematic analysis were applied to qualitative data. The 2019–2020 quantitative data identified no statistically signficant variations. There was no evidence Māori provider experiences improved, but generic providers reported less favourable conditions. Qualitative data revealed providers remain dependent on individual managers and there was inconsistency across providers that could be addressed by transparent quality assurance. Māori providers were frustrated by contracting environments. They wanted to be recognised as Te Tiriti o Waitangi partners, with flexibility, certainty of investment (longer contracts), support (infrastructure investment) to be able to meet the high needs of their communities. This nationwide survey was completed prior to the current health reforms but implications are considered for the Māori Health Authority.
This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives License (http://creativecommons.org/licenses/by-nc-nd/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited, and is not altered, transformed, or built upon in any way.